Mechanistic Insights Into the Association Between Gut Microbiota Diversity and Atherosclerosis, Acute Coronary Syndrome, and Peripheral Arterial Disease Progression - Amr Ali Mohamed Abdelgawwad El‐Sehrawy; Usamah Sayed; Zarina Nasirova; Quvonch Tursunov; Omer Qutaiba B. Allela; Lara Asim Kzar; Rajashree Panigrahi; Neeraj Bainsal (Clinical Cardiology, 2026)
ABSTRACT Background The gut microbiome has emerged as a potential contributor to cardiovascular diseases (CVDs), including atherosclerosis, acute coronary syndrome (ACS), and peripheral arterial disease (PAD). While observational studies link dysbiosis to CVD, causal relationships remain uncertain. Methods This narrative review synthesizes evidence from human observational studies, clinical interventions, and experimental models to distinguish association from mechanistic plausibility and clinical causality. Literature was searched through July 2026 in PubMed/MEDLINE, Web of Science, and Scopus. Results Microbial metabolites—including trimethylamine N‐oxide (TMAO), short‐chain fatty acids (SCFAs), bile acids, and lipopolysaccharide (LPS)—modulate endothelial function, immune cell programming, platelet activity, and plaque stability through receptor‐mediated signaling and epigenetic regulation. SCFAs demonstrate potentially protective effects via GPCR and HDAC pathways, while TMAO is associated with atherothrombotic risk. However, much mechanistic evidence derives from preclinical studies. Heterogeneity from diet, geography, host characteristics, renal function, and medications substantially influences microbiota‐CVD associations. Conclusion The gut‐vascular connection is biologically plausible, but definitive clinical causality remains unproven. Microbiome‐directed therapies (dietary modulation, pre/pro/synbiotics, targeted metabolite inhibition) are investigational. Prospective, standardized, adequately powered human studies with clinically meaningful outcomes are essential before routine cardiovascular application.